2018
DOI: 10.1097/igc.0000000000001175
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes After Gestational Trophoblastic Neoplasia. A Comparison Between Single-Agent and Multiagent Chemotherapy

Abstract: Except for the risk of premature ovarian failure, a rare adverse effect of combined treatments, both single-agent and multiagent chemotherapy can be safely administered to patients with a desire for childbearing. High-risk patients have worse reproductive outcomes because they undergo hysterectomy more frequently than low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…However, we were unable to perform a sub-group analysis among women with a desire for future pregnancy. Therefore, this evidence should be interpreted with caution given that the pregnancy desire has a significant impact on the probability to attain future pregnancy 6. Of note, the recent MITO-9 study demonstrated a non-significant difference in pregnancy rate between the single- and multi-agent chemotherapy groups in women with a desire for pregnancy 6…”
Section: Discussionmentioning
confidence: 91%
“…However, we were unable to perform a sub-group analysis among women with a desire for future pregnancy. Therefore, this evidence should be interpreted with caution given that the pregnancy desire has a significant impact on the probability to attain future pregnancy 6. Of note, the recent MITO-9 study demonstrated a non-significant difference in pregnancy rate between the single- and multi-agent chemotherapy groups in women with a desire for pregnancy 6…”
Section: Discussionmentioning
confidence: 91%
“…Cioffi et al and Wong et al both reported a 97.5-100% rate menstrual recovery after methotrexate for low-risk gestational trophoblastic neoplasia. [31][32][33] Reports on ovarian function after single-agent actinomycin-D are more difficult to find. Most studies report on actinomycin-D in combination with other drugs or as second-line treatment after methotrexate failure.…”
Section: Fertility and Reproductive Outcomes After Single-agent Chemomentioning
confidence: 99%
“…40 Blagden et al found higher conception rates in women in the single-agent group who conceived within a year after completion of treatment, 36 while no difference in pregnancy rate between single-or multi-agent chemotherapy was found in a recent MITO-9 analysis. 31 Studies comparing pregnancies in women who conceived within 6 months after completion of chemotherapy with those who conceived later, noted a higher rate of spontaneous abortions in early conceptions. However, these studies did not separate outcomes after singleand multi-agent chemotherapy.…”
Section: Fertility and Reproductive Outcomes After Single-agent Chemomentioning
confidence: 99%
“…It can influence future fertility or early menopause of women (15). The main risk factors related to GTN progression include previous molar pregnancy, within the age of 40 years and above, and Asian and American ancestry (16). Unfortunately, no comprehensive view is available with respect to epidemiological aspects, clinical features, and treatment outcomes of patients suffering from gestational trophoblastic tumors in our country.…”
Section: Resultsmentioning
confidence: 99%